Meaningful Access for Indigents on Death Row: Giarratano v. Murray and the Right to Counsel in Post-conviction Proceedings - Brooks, William H. (1990)
In 1932 the United States Supreme Court held that the states must provide free legal counsel to indigent defendants in capital cases.' Since then the Court has continued to define the scope of an indigent death row defendant's right to counsel at various critical stages of the defendant's trial and appeal. Following a direct appeal to the state court of appeals and state supreme court, an inmate on death row may seek a writ of certiorari from the United States Supreme Court. A prisoner is not entitled to state appointed counsel for that action. Next, the defendant may seek post-conviction relief in state court or in federal court if state remedies have been exhausted. Until recently,however, the question remained whether the Constitution provides indigent death row inmates with state appointed counsel and financial assistance in postconviction proceedings that collaterally attack the validity of a conviction, such as habeas corpus actions brought in state and federal court. Under constitutional law and statutory provisions, capital defend-ants are entitled to pursue certain postconviction remedies; nevertheless, an indigent death row inmate traditionally has not been entitled to a state appointed lawyer for these proceedings. In Giarratano v. Murray the Supreme Court held that an individual appointment of an attorney to represent an indigent death row defendant throughout the process is not constitutionally required to fulfill the right of meaningful access to the courts. Prior to Giarratano several district courts and circuit courts of appeals had disagreed over the scope of the right of access and the necessity for attorney assistance or appointment.' The United States Supreme Court has recognized that prisoners have a constitutional right of access to the courts. The scope of that right provides one rationale for determining whether indigent defend-ants on death row are entitled to state appointed counsel for the purpose of pursuing postconviction remedies.'0 This issue is especially relevant to inmates on death row because of the severity and finality of the sentence